THE EFFECT OF LIQUIDITY, SOLVENCY, PROFITABILITY AND ACTIVITY ON COMPANY VALUE: (Study of Food and Beverage Sub-sector Manufacturing Companies Listed on the Indonesian Stock Exchange for the 2019-2022 Period) - Kurniawan, Yogi Ade Tia (Transpublika Publisher, 2024)
The stock trading value in the Indonesian capital market increased by 15.1% to IDR 9,499 trillion in 2022. The food and beverage industry in the manufacturing sector is key to Indonesia's economic growth, showing consistent growth of over 20% in 2022. This industry's success is due to its capital capacity, workforce absorption, and added value creation. This study investigates the impact of Liquidity, Solvency, Profitability, and Activity on the Corporate Valuation of publicly listed food and beverage manufacturing companies on the IDX from 2019 to 2022. Data extracted from the financial records of companies was employed in a method that focused on numbers, cause-and-effect relationships, and connections. A purposive sampling process was used to choose 24 companies for examination. The analysis of the data involved the use of multiple linear regression. The results suggest that the combined independent factors have an impact on the value of a company. Specifically, the level of liquidity, as determined by various ratios such as the current ratio, quick ratio, and cash ratio, has a considerable influence on the company's value as measured by PBV. The debt-to-equity ratio (DER) and long-term debt-to-equity ratio (LTDtER) have a notable influence on solvency, unlike the debt asset ratio (DAR). Company value is greatly affected by return on equity (ROE) and return on assets (ROA), but not by net profit margin (NPM) when it comes to profitability. Lastly, Activity, measured by inventory turnover (PPe), significantly affects company value, whereas receivables turnover (PPi) does not.